(untitled) (Revista de Investigaciones Universidad del Quindío, 2023)
Background: COVID-19 pandemic has affected all the world. The consequence of the COVID-19 infection causes many disorders in many organs, one of them is the placenta. COVID-19 disease has long-term effects on various tissues after recovery. The aim of this study was to investigate the placentas of pregnant women with healthy, COVID-19 positive during the second trimester and labor. Material and methods: A total of twenty-four pregnant women (8 patients per each group) were included in the study. Their placentas were processed for routine paraffin wax embedding protocol. The blood parameters of patients were recorded. Placental tissues were stained with hematoxylin-eosin dye and immune stained with TNF-α and ADAMTS-8. Statistical analysis was performed on blood and histological parameters. Results: AST and CRP values of biochemical parameters were higher in women with second trimester and labor groups than in the healthy group. Also, a significant increase in ALT values was observed in the labor group. Normal histology was observed in the placentas of healthy patients. More histopathology was recorded in the placentas of COVID-19 infected women compared to healthy placentas. The expression of TNF-α and ADAMTS-8 were found significantly higher in the COVID-19 placentas compared to the non-COVID-19 group. Conclusions: COVID-19 infection can cause pathological changes during pregnancy and labor. This study shows that COVID-19 not only acutely has adverse effects on placental pathologies but also has long-term effects. TNF-α and ADAMTS-8 primary antibodies can be a guide in demonstrating these effects.